PEMANFAATAN TUMBUHAN SEBAGAI OBAT TRADISIONAL OLEH ETNIS TO BALAESANG DI DESA RANO, KABUPATEN DONGGALA, SULAWESI TENGAH: Traditional Usage of Plant as Medicine by “To Balaesang” Ethnic In the Donggala District, Central Sulawesi - Ramadanil Pitopang; Dandy Prayoga; PUTI ANDALUSIA BANILAI; Moh Iqbal (Biocelebes, 2022)
This paper discusses the result of the study on "traditional plant use as medicine by the Balaesang tribal community in Rano village, Balaesang, Donggala district, Central Sulawesi", Indonesia. The research was conducted from December 2020 to March 2021. The basic data of traditional plant used by local ethnic were collected through an in-depth interview initiated by an informed consent using a questionnaire containing open-ended questions. A snowball technique was used to obtain appropriate respondents including the village leader and traditional healers. The results showed that there were 42 plants species (consist of 26 families) that are used as traditional medicine by the Balaesang tribe. Some of plants were utilized for beauty purpose, chronic diseases, skin, hypertension, gastrovascular and other diseases. The preparation method is boiled, ground, consumed directly, squeezed, smeared, and chewed